Binding of ligands to the aryl hydrocarbon receptor: An overview of methods - Hrubý, Jiří; Dvořák, Zdeněk (Toxicology letters, 2025)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor, which plays numerous and pivotal roles in human physiology and pathophysiology. Therefore, pharmacotherapeutic targeting of the AhR is a highly pertinent issue. The identification of new AhR ligands and the characterization of the interactions between the AhR ligands and AhR protein requires appropriate methodology. In spite the AhR is monomeric intracellular soluble receptor, the full-length human AhR protein has not been crystallized so far, and its isolation in a form applicable in the binding assays is highly challenging. Recent advances, including crystallization of AhR fragments, recombinant protein technologies, and cryogenic electron microscopy, allowed for exploitation of diverse experimental techniques for studying interactions between ligands and the AhR. In the current paper, we review existing AhR ligand binding assays, including their description, applicability and limitations.
Keywords: Protein Binding; interactions; Ligands; transkripční faktory bHLH; aryl hydrocarbon receptor; Animals; Humans; ligandy; protein binding; lidé; receptory aromatických uhlovodíků; ligands; zvířata; Receptors, Aryl Hydrocarbon; vazba proteinů; Basic Helix-Loop-Helix Transcription Factors